2008
DOI: 10.1097/01.ncq.0000336673.02725.ec
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Acute Confusion Protocol

Abstract: This evidence-based project was undertaken to implement research-based preventive protocols to decrease the negative outcomes associated with delirium/acute confusion. After implementation, the medical-surgical unit experienced a 62% reduction in falls and a 100% decrease in sitter usage the first year. The use of medications known to cause acute confusion was decreased by more than 50%. Since implementation, the fall rate as well as the use of restraints has decreased by 25%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Twelve studies of the HELP model 10,17,18,20,2225,28,29,53,54 measured delirium incidence. In total, the meta-analysis involved 3,605 patients and showed that the odds of delirium were 53% lower in the intervention group compared with controls (OR 0.47; 95% CI, 0.37–0.59, I 2 = 28%).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies of the HELP model 10,17,18,20,2225,28,29,53,54 measured delirium incidence. In total, the meta-analysis involved 3,605 patients and showed that the odds of delirium were 53% lower in the intervention group compared with controls (OR 0.47; 95% CI, 0.37–0.59, I 2 = 28%).…”
Section: Resultsmentioning
confidence: 99%
“…They have developed terms unique to their countries and disciplines. Examples include Rogers' work [5] in diffusion of innovations in rural sociology starting in the 1940s in the United States, nursing research utilization also in the United States [6], KT and knowledge transfer in Canada [7], research capacity in the United Kingdom [8], and the know-do gap in Australia [9]. …”
Section: Introductionmentioning
confidence: 99%